2021
DOI: 10.3389/fmars.2021.800087
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Occurrence Characteristics of Microplastics in Typical Maize Farmland Soils With Long-Term Plastic Film Mulching in Northern China

Abstract: Microplastics pollution has been threatening the global environmental security, in which agricultural activities are considered as a main source of microplastics occurrence in soils. However, little is known about the occurrence characteristics of microplastics in agricultural soils with long-term plastic film mulching. Therefore, the abundance, distribution, and composition of microplastics were investigated by analyzing 225 soil samples collected from typical maize (Zea mays L.) planting zones with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Zhou et al (2020) reported 571 particles kg −1 from sites where plastic mulch film was used, compared with 263 particles kg −1 , where no‐mulch was used. Similar observations were made by Zhang et al (2021), recording 376 ± 149 particles kg −1 at sites where plastic mulch film was used, and 754 ± 477 particles kg −1 at non‐mulched sites. There are no comparable surveys of microplastic concentrations agricultural soils in Europe.…”
Section: Discussionsupporting
confidence: 88%
“…Zhou et al (2020) reported 571 particles kg −1 from sites where plastic mulch film was used, compared with 263 particles kg −1 , where no‐mulch was used. Similar observations were made by Zhang et al (2021), recording 376 ± 149 particles kg −1 at sites where plastic mulch film was used, and 754 ± 477 particles kg −1 at non‐mulched sites. There are no comparable surveys of microplastic concentrations agricultural soils in Europe.…”
Section: Discussionsupporting
confidence: 88%
“…This cascaded plastic waste processing after EoL waste disposal may benefit from onsite monomer, fuels, energy production, and debris mitigation, but it lacks quantitative understanding in the existing literature. We study the thermoplastic that is most widely produced (57% of total plastic manufactured) in the U.S. 34 and specifically focuses on PP in plastic bags because of its similar chemical property to other polyolefins widely used in packagings 35 as the major plastic pollution sources, 36 and identical EoL waste treatment methods to other polymeric materials. The compartment transport and degradation kinetics are accounted for to determine the extent of plastic pollution, 37 which denotes the full-spectrum environmental burdens of material losses and their derived chemical releases in a certain time frame.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the “white pollution” caused by the widespread use of mulch is becoming increasingly prominent ( Liu et al., 2014 ; Zhang et al., 2021 ; Li et al., 2021 ). As an economically important crop, cotton is mainly planted with film mulching in Xinjiang, China.…”
Section: Introductionmentioning
confidence: 99%